Survival kit for the afterlife or instruction manual for prehistorians? Staging artefact production in Middle Neolithic cemetery Kadruka 23, Upper Nubia, Sudan. (December 2021) - Alarashi, Hala; Gourichon, Lionel; Khalidi, Lamya; Chambon, Philippe; Sellier, Pascal; Maines, Emma; Aoudia, Louiza; Anderson, Patricia; Baumann, Malvina; Langlois, Olivier
Abstract: Abstract : The burials at the Neolithic cemetery Kadruka 23 in Sudan have yielded adornments and bone and lithic artefacts that occur as distinct stages of the chaîne opératoire . This article reports on a hitherto unrecognised funerary practice that highlights the importance of craftsmanship for Neolithic communities in life and beyond.